2015
DOI: 10.2337/dc14-2319
|View full text |Cite
|
Sign up to set email alerts
|

Selective Insulin Resistance in Homeostatic and Cognitive Control Brain Areas in Overweight and Obese Adults

Abstract: OBJECTIVEImpaired brain insulin action has been linked to obesity, type 2 diabetes, and neurodegenerative diseases. To date, the central nervous effects of insulin in obese humans still remain ill defined, and no study thus far has evaluated the specific brain areas affected by insulin resistance. RESEARCH DESIGN AND METHODSIn 25 healthy lean and 23 overweight/obese participants, we performed magnetic resonance imaging to measure cerebral blood flow (CBF) before and 15 and 30 min after application of intranasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
155
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 39 publications
(28 reference statements)
10
155
0
5
Order By: Relevance
“…44,46 Whether insulin secreted after glucose uptake is responsible for this effect has not been shown conclusively in all studies. 41,42 However, two studies in the past few years have shown similar hypothalamic effects after intranasal insulin, 47,48 underscoring that the human hypothalamus reacts to insulin. Glucoseresponsive and insulinresponsive neurons have been localized to the hypothalamus; therefore, the human hypothalamus probably responds to both signals.…”
Section: Insulin-responsive Brain Areasmentioning
confidence: 95%
See 3 more Smart Citations
“…44,46 Whether insulin secreted after glucose uptake is responsible for this effect has not been shown conclusively in all studies. 41,42 However, two studies in the past few years have shown similar hypothalamic effects after intranasal insulin, 47,48 underscoring that the human hypothalamus reacts to insulin. Glucoseresponsive and insulinresponsive neurons have been localized to the hypothalamus; therefore, the human hypothalamus probably responds to both signals.…”
Section: Insulin-responsive Brain Areasmentioning
confidence: 95%
“…12 This phenomenon is often referred to as brain insulin resistance. 103,104 The association of increased body weight with impaired insulin action has since been replicated in a number of studies using magnetoencephalography 21,23 and has been localized by fMRI 48,105 and PET. 16 The importance of body weight for brain metabolism is further underlined by the dis covery that insulininduced brain activity in people with obesity normalizes when they lose weight after bariatric surgery.…”
Section: Effects On Peripheral Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…In studies in humans with IR, IN or intravenous insulin application did not induce brain activity in the insulinsensitive brain areas, i.e., the hippocampus, prefrontal cortex, fusiform gyrus, and hypothalamus, as measured by noninvasive brain imaging tools (16,17). Although such evidence for the activation of insulin-sensitive brain regions has not yet been demonstrated after diazoxide administration, the study by Esterson et al (15) adds to the discussion on impaired central regulation of glucose and energy metabolism in type 2 diabetes (11).…”
mentioning
confidence: 99%